Response of Growth and Production of Corn (Zea Mays L) with Liquid Fertilizer in Labuhan Batu Regency - Harahap, Fitra Syawal Harahap; Walida, Hilwa; Harahap, Dahrul Aman; Oesman, Roswita; Fadhillah, Wizni (Jurnal Online Pertanian Tropik, 2019)
Growth and Production of Corn Plants (Zea mays L) with Provision of liquid supplementary fertilizer (PPC) is an alternative fertilizer that can increase plant growth and production. The constituents of the nutrients can provide elements that are not present in the soil. This study aims to get the right dose for growth and production of corn (Zea mays L). The treatment consists of 7 levels O0 = N, P, K Recommended dosage (Urea = 5 g / array; TSP = 2.50 g / KCl array = 1.87 g / array) O1 = Standard organic compost / fertilizer (gr / plot) ) + N, P, K (Urea = 5 g / bolt; TSP = 2.50 g / bolt; KCl = 1.87 g / bolt) O2 = 0.75 ml Primatan + N, P, K (Urea = 5 g / run; TSP = 2.50 g / run; KCl = 1.87 g / run) P3 = 1.12 ml Primate + N, P, K (Urea = 5 g / run; TSP = 2.50 g / extract; KCl = 1.87 g / extract) O4 = 1.5 ml Primatan + N, P, K (Urea = 5 g / extract; TSP = 2.50 g / extract; KCl = 1.87 g / array) O5 = 1.5 ml Primatan + 0.75 N, P, K (urea = 3.75 g / run; TSP = 1.87 g / run; KCl = 0.14 g / run) O6 = 1.5 ml primatan + 0.50 N, P, K (urea = 2.50 g / bolt; TSP = 1.25 g / bolt; KCl = 0.93 g / bolt). Treatment P2 = 0.75 ml Primatan + N, P, K (Urea = 5 g / line; TSP = 2.50 g / line; KCl = 1.87 g / line) is able to give the best results for all parameters, namely plant height amounting to 44.09 cm, leaf area 241.19 mm3, biomass weight per plant sample 271.50 g, selling fresh weight 225.50 g, total chlorophyll 30.93units / 6 mm3.